Предмет: Алгебра, автор: smolinegor31

(а+3)(а-2)-(а+4)(а-1)=3а

Ответы

Автор ответа: bokachi38
0

(a + 3)(a - 2) - (a - 4)(a - 1) = 3a \\ a \times a + a \times ( - 2) + 3 \times a + 3 \times ( - 2) - (a \times a   + a \times ( - 1)+ ( - 4) \times a + ( - 4) \times ( - 1)) = 3a \\  {a}^{2}  - 2a + 3a - 6 - ( {a}^{2}  - a - 4a + 4) = 3a \\  {a}^{2}  - 2a + 3a - 6 -  {a}^{2}  + a + 4a - 4 = 3a \\  - 2a + 3a + a + 4a - 3a = 6 + 4 \\ 3a = 10 \\ a =  \frac{10}{3}  \\ a = 3 \frac{1}{3}

Похожие вопросы
Предмет: Қазақ тiлi, автор: mansurjanerke